Effect of maturation on the resistance of rat hearts against ischemia. Study of potential molecular mechanisms - Griecsová, L; Farkašová, V; Gáblovský, I; Khandelwal, V K M; Bernátová, I; Tatarková, Z; Kaplan, P; Ravingerová, T (Physiological research, 2015)
Reduced tolerance to ischemia/reperfusion (IR) injury has been shown in elder human and animal hearts, however, the onset of this unfavorable phenotype and cellular mechanisms behind remain unknown. Moreover, aging may interfere with the mechanisms of innate cardioprotection (preconditioning, PC) and cause defects in protective cell signaling. We studied the changes in myocardial function and response to ischemia, as well as selected proteins involved in "pro-survival" pathways in the hearts from juvenile (1.5 months), younger adult (3 months) and mature adult (6 months) male Wistar rats. In Langendorff-perfused hearts exposed to 30-min ischemia/2-h reperfusion with or without prior PC (one cycle of 5-min ischemia/5-min reperfusion), we measured occurrence of reperfusion-induced arrhythmias, recovery of contractile function (left ventricular developed pressure, LVDP, in % of pre-ischemic values), and size of infarction (IS, in % of area at risk size, TTC staining and computerized planimetry). In parallel groups, LV tissue was sampled for the detection of protein levels (WB) of Akt kinase (an effector of PI3-kinase), phosphorylated (activated) Akt (p-Akt), its target endothelial NO synthase (eNOS) and protein kinase Cepsilon (PKCepsilon) as components of "pro-survival" cascades. Maturation did not affect heart function, however, it impaired cardiac response to lethal IR injury (increased IS) and promoted arrhythmogenesis. PC reduced the occurrence of malignant arrhythmias, IS and improved LVDP recovery in the younger animals, while its efficacy was attenuated in the mature adults. Loss of PC protection was associated with age-dependent reduced Akt phosphorylation and levels of eNOS and PKCepsilon in the hearts of mature animals compared with the younger ones, as well as with a failure of PC to upregulate these proteins. Aging-related alterations in myocardial response to ischemia may be caused by dysfunction of proteins involved in protective cell signaling that may occur already during the process of maturation.
Keywords: ischemické přivykání; Signal Transduction; fosforylace; srdeční arytmie; funkce levé komory srdeční; synthasa oxidu dusnatého, typ III; potkani Wistar; fyziologická adaptace; myokard; Ischemic Preconditioning, Myocardial; reperfuzní poškození myokardu; Male; komorový tlak (srdce); modely nemocí na zvířatech; Myocardium; infarkt myokardu; Rats, Wistar; Arrhythmias, Cardiac; Coronary Circulation; Recovery of Function; Proto-Oncogene Proteins c-akt; časové faktory; stárnutí; Disease Models, Animal; Aging; proteinkinasa C-epsilon; srdeční frekvence; Protein Kinase C-epsilon; Adaptation, Physiological; koronární cirkulace; věkové faktory; Heart Rate; Isolated Heart Preparation; Nitric Oxide Synthase Type III; Phosphorylation; obnova funkce; zvířata; preparace izolovaného srdce; mužské pohlaví; Age Factors; Animals; Myocardial Reperfusion Injury; Time Factors; protoonkogenní proteiny c-akt; Myocardial Infarction; Ventricular Function, Left; signální transdukce; Ventricular Pressure